2014
DOI: 10.1002/bdrc.21077
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of neural crest‐derived stem cells for ocular repair

Abstract: Whether it is due to a particular epigenetic signature, or some other component of an embryonic differentiation program, accumulating evidence indicates that the origins of a stem cell has a profound impact on the potential of a tissue to regenerate and repair. Here, we focus on Müller glia, long considered the stem cells of the retina, and their surprising derivation from the neural crest. Whether the multipotent properties of a subset of Müller glia is associated with their neural crest origin remains a tant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 91 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…Although Müller cells share a lineage with retinal neurons, their time of birth appears to be different. Recent studies found the surprising origin of Müller cells in the neuronal crest cells (Liu et al, 2014a). Birth dating of retinal neurons and Müller cells was determined by 3 H-thymidinelabelling (Sidman, 1961) and all retinal cell types are generated in an orderly fashion, the sequence of which is largely conserved among vertebrates (Vecino and Acera, 2015).…”
Section: Origin and Morphology Of Müller Cellsmentioning
confidence: 99%
“…Although Müller cells share a lineage with retinal neurons, their time of birth appears to be different. Recent studies found the surprising origin of Müller cells in the neuronal crest cells (Liu et al, 2014a). Birth dating of retinal neurons and Müller cells was determined by 3 H-thymidinelabelling (Sidman, 1961) and all retinal cell types are generated in an orderly fashion, the sequence of which is largely conserved among vertebrates (Vecino and Acera, 2015).…”
Section: Origin and Morphology Of Müller Cellsmentioning
confidence: 99%
“…Hence, autologous HFBSCs are potentially suitable for therapeutic application in a broad range of neurological disorders such as ALS, Alzheimer’s disease and stroke. They also may be used in cell-based therapies for sensory neurological diseases such as those for ocular or inner ear regeneration (Liu et al 2014 ; Huisman and Rivolta 2012 ). If HFBSCs could be harvested from plucked hairs, their practical utilization for autologous stem cell therapy would increase immensely.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a recent lineage study in the mouse suggests that a subset of Müller cells may be derived from the neural crest (Liu et al, 2014). This is quite unexpected and thus clearly deserves further investigation and comparative studies in different vertebrate species.…”
Section: The Müller Cell: More Than Just a Glial Cellmentioning
confidence: 99%
“…As mentioned above, a recent study suggested that a subset of Müller cells in the mouse retina may derive from the neural crest (Liu et al, 2014). This is quite surprising and contrasts with results of most neural crest lineage tracing studies and with previous evidence that Müller glia is exclusively derived from the retinal neuroepithelium.…”
Section: Müller Cell Response To Injury In Mammalsmentioning
confidence: 99%
See 1 more Smart Citation